Factors Affecting Behaviour of Paying Zakat in Greater Jakarta Indonesia - Anton, Hindarjo; Juhary, Ali; Owin Jamasy, Djamaludin; Taufik, Hidayat; Willson, Gustiawan; Mardiyana; Muhammad, Doddy (2022)
The potential of Zakat and Zakat collected in Indonesia are very different. This gap occurs due to a lack of public awareness of the responsibility of Zakat, lack of trust in zakat institutions, lack of socialization of Zakat, and lack of acceptance and use of ideal technology to pay Zakat. This study's primary purpose is to determine the elements that influence the intention to pay Zakat. This study creates a model by integrating aspects of integrated marketing communication and the use of technology as independent variables. Sampling was used to collect 400 respondents among zakat payers who met the set criteria. The findings reveal that the use and application of diverse technologies and integrated marketing communications are associated with outcomes. This study adds to the model specification repertoire. Therefore, this research approach is important to bring new insights into model specifications.